Field Agricultural Extension Workers’ Influence as Mediators on The Success of Strategic Irrigation Modernization and Urgent Rehabilitation Project (SIMURP) program - Aisyah, Siti; Faqih, Achmad; Komala, Ratna; Aini, Nurjibbah; Dewi, Rima Merliana; Alamsyah, Rio (Devotion : Journal of Research and Community Service, 2023)
-